Right ventricular outflow tract low‐voltage areas identify the site of origin of idiopathic ventricular arrhythmias: A high‐density mapping study. (22nd September 2019) - Letsas, Konstantinos P.; Efremidis, Michael; Vlachos, Konstantinos; Asvestas, Dimitrios; Takigawa, Masateru; Bazoukis, George; Frontera, Antonio; Giannopoulos, George; Saplaouras, Athanasios; Sakellaropoulou, Antigoni; Mililis, Panagiotis; Dragasis, Stylianos; et al.
Abstract: Introduction: Electronatomical mapping allows direct and accurate visualization of myocardial abnormalities. This study investigated whether high‐density endocardial bipolar voltage mapping of the right ventricular outflow tract (RVOT) during sinus rhythm may guide catheter ablation of idiopathic ventricular arrhythmias (VAs). Methods and Results: Forty‐four patients (18 males, mean age: 38.1 ± 13.8 years) with idiopathic RVOT VAs and negative cardiac magnetic resonance imaging underwent a stepwise mapping approach for the identification of the site of origin (SOO). High‐density electronatomical mapping (1096.6 ± 322.3 points) was performed during sinus rhythm and identified at least two low bipolar voltage areas less than 1 mV (mean amplitude of 0.20 ± 0.10 mV) in 39 of 44 patients. The mean low‐voltage surface area was 1.4 ± 0.8 cm 2 . Group 1 consisted of 28 patients exhibiting low‐voltage areas and high‐arrhythmia burden during the procedure. Pace match to the clinical VAs was produced in one of these low‐voltage areas. Activation mapping established the SOO at these sites in 27 of 28 cases. Group 2 comprised 11 patients exhibiting abnormal electroanatomical mapping, but very low‐arrhythmia burden during the procedure. Pace mapping produced a near‐perfect or perfect match to the clinical VAs in one of these areas in 9 of 11 patients which was marked as potential SOO and targeted for ablation. During the follow‐up period, 25 of 28 patients from group 1 (89%) and 7 of 9 patients from group 2 (78%) were free from VAs. Conclusions: Small but detectable very low‐voltage areas during mapping in sinus rhythm characterize the arrhythmogenic substrate of idiopathic RVOT VAs and may guide successful catheter ablation.